2007
DOI: 10.4141/cjps07136
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of enzymatic browning in selected apple genotypes

Abstract: S. 2007. Biochemical characterization of enzymatic browning in selected apple genotypes. Can. J. Plant Sci. 87: 1067-1074. Enzymatic browning in apples (Malus × domestica Borkh.) caused by polyphenol oxidases (PPO) is the major factor responsible for the deterioration of quality in processed apple products such as juice, fresh-cut slices, and chips. Selected apple genotypes with a range of low post-cut enzymatic browning were investigated to understand the biochemical mechanisms leading to enzymatic browning. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 37 publications
3
16
1
Order By: Relevance
“…The maximum ascorbic acid content was recorded in red cultivars, 'Starkrimson' (32.08 mg 100 g -1 ) and 'Oregon Spur II' (31.76 mg 100 g -1 ) whereas the least ascorbic acid was recorded in 'Well Spur' (19.38 mg 100 g -1 ) ( Table 2). Our data on this attribute are lower than those reported by Jan et al (2012) and have wider range than those reported by Joshi et al (2007) who reported ascorbic acid in the range of 14.3-45.9 mg 100 g -1 and 10.27-12.49 mg 100 g -1 , respectively in apples. This deviation in the values of ascorbic acid may be due to fact that we analyzed different varieties than those studied by them.…”
Section: Ascorbic Acid Antioxidant (Aox) Activity and Total Carotenoidcontrasting
confidence: 85%
See 1 more Smart Citation
“…The maximum ascorbic acid content was recorded in red cultivars, 'Starkrimson' (32.08 mg 100 g -1 ) and 'Oregon Spur II' (31.76 mg 100 g -1 ) whereas the least ascorbic acid was recorded in 'Well Spur' (19.38 mg 100 g -1 ) ( Table 2). Our data on this attribute are lower than those reported by Jan et al (2012) and have wider range than those reported by Joshi et al (2007) who reported ascorbic acid in the range of 14.3-45.9 mg 100 g -1 and 10.27-12.49 mg 100 g -1 , respectively in apples. This deviation in the values of ascorbic acid may be due to fact that we analyzed different varieties than those studied by them.…”
Section: Ascorbic Acid Antioxidant (Aox) Activity and Total Carotenoidcontrasting
confidence: 85%
“…In a similar study, Wang et al (2015) reported that the antioxidant activity was significantly higher for red-fleshed genotypes than for white-fleshed genotypes. Similarly, a wider range of AOX activity (7.7-22.6 lmol Trolox equivalent g -1 ) has been reported by Joshi et al (2007) in apple cultivars. The difference observed among the genotypes studied in terms of antioxidant activity may probably be due to plant genotype because all plants were grown in the same location using similar horticultural practices.…”
Section: Ascorbic Acid Antioxidant (Aox) Activity and Total Carotenoidmentioning
confidence: 51%
“…Air‐drying caused significant loss of catechin, epicatechin and phloridzin, which can be due to the exposure of apple slices to oxygen during air‐drying resulting in postcut enzymatic browning in apple slices (Funebo and Ohlsson 1998). It has been reported that catechin and epicatechin are the desirable substrates for polyphenol oxidase, which causes postcut enzymatic browning in apples (Joshi et al. 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Air-drying caused significant loss of catechin, epicatechin and phloridzin, which can be due to the exposure of apple slices to oxygen during air-drying resulting in postcut enzymatic browning in apple slices (Funebo and Ohlsson 1998). It has been reported that catechin and epicatechin are the desirable substrates for polyphenol oxidase, which causes postcut enzymatic browning in apples (Joshi et al 2007). However, in the present study, the impact of drying on the color and browning of the apple slices could not be determined because of the interference of the color measurement due to the characteristic nonuniform red and white color distribution of the red-fleshed apple slices.…”
Section: Resultsmentioning
confidence: 99%
“…4a and b ). The observed differences in the two apple varieties may be due to the differences in the susceptibility to browning of the apple varieties (Lozano-de-Gonzalez et al, 1993;Rocha & Morias, 2001;Ye, Heng, Yuan-peng, Feng & Shu-wei, 2007;Joshi et al, 2007), PPO activities and perhaps differences in polyphenol composition (Joshi, Rupasinghe, Pitts & Khanizadeh, 2007). In HPP (100-1000 MPa/−20°C to 60°C), cell walls and membranes are prone to disruption (Michel & Autio, 2001;Prestamo & Arroyo, 1998;Van Buggenhout, Messagie, Van Loey, & Hendrickx, 2005).…”
Section: Total Colour Change (δE) and Visual Browning After Air Exposurementioning
confidence: 96%